Semantic Study of the Meaning of Pantun in Traditional Malay Tamiang Wedding Ceremonies as an Effort to Preserve Local Culture - Hariadi, Joko; Fajarini, Indah; Fadhilah, Muhammad Arif; Amelia, Nur; Tamara, Widia; Liasna, Tanita (Universitas Muhammadiyah Malang, 2025)
Pantun, as an integral part of the Tamiang Malay traditional wedding ceremony, has complex cultural meanings, but its existence is often only understood superficially and aesthetically. The main problem in this study is the lack of in-depth documentation of the semantic meaning of pantun, especially in terms of its denotative and connotative aspects, which hinders efforts to preserve this oral tradition. This study aims to describe and analyze the denotative and connotative meanings of pantun used in traditional Tamiang Malay wedding ceremonies to preserve local culture. The study uses a descriptive qualitative approach with participatory observation, in-depth interviews with traditional leaders, and audiovisual documentation of wedding ceremonies. The data were analyzed using Roland Barthes' lexical semantics and semiotics theories to explore the literal and symbolic structures in the pantun. The study results show that the Tamiang traditional pantun not only functions as a medium of ritual communication but also as a representation of local values such as honor, politeness, gender equality, and obedience to traditional norms. The connotative meaning of pantun serves as a collective instrument in shaping intergenerational cultural awareness. This study concludes that traditional pantun has excellent potential as a medium for preserving cultural identity, so it is important to continue to revive, document, and introduce it widely, both in academic and social contexts. This study also enriches the field of cultural semantics and provides a theoretical and practical basis for research on oral traditions in other indigenous communities.